Implementation of Behavioristic Shaping and Modeling Techniques in Differentiated Learning for 5th Grade Elementary School - Rostiana, Nina; Riyadi, Arie Rakhmat (International Conference on Elementary Education, 2025)
This study aims to describe and analyze the implementation of shaping and modeling techniques in differentiated learning for fifth-grade elementary school students. The background of this research is based on the need for a learning approach that not only builds positive learning behaviors but also adapts to the diverse characteristics, interests, and abilities of students, as emphasized in theMerdeka Curriculum. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings indicate that the shaping technique, implemented through gradual task assignments from easy to difficult, enhances students’ learning motivation. Meanwhile, the modeling technique, in which the teacher demonstrates examples, effectively supports students in understanding the learning material. Moreover, students expressed awareness of diverse learning styles and felt that the teacher's instructional methods suited their individual learning needs. Thus, the implementation of these two behaviorist techniques supports adaptive, engaging, and responsive differentiated learning in elementary education.